Penilaian Pendidikan Agama Islam Berbasis Kecakapan Abad ke-21 pada Peserta Didik Digital Native - Nurul Aulia; Erwin Mahrus; Muhammad Tisna Nugraha (Kartika: Jurnal Studi Keislaman, 2026)
The development of digital technology has given rise to a generation of digital natives who possess different learning characteristics compared to previous generations. This condition requires adjustments in teaching and learning practices, including the assessment of Islamic Religious Education (PAI). Therefore, 21st-century skills encompassing critical thinking, creativity, collaboration, and communication have become essential competencies that need to be integrated into the PAI assessment system. This study aims to analyze and formulate a concept of PAI assessment based on 21st-century skills that is relevant to the characteristics of digital natives. The research employs a qualitative approach through a literature study by examining books, journal articles, and relevant scientific documents.The results of the study indicate that valid PAI assessment for digital natives should be designed in an authentic, contextual, and technology-based manner, integrating cognitive, affective, and psychomotor aspects in a balanced way. Assessment should not only focus on the mastery of religious knowledge but also on students’ ability to internalize and implement Islamic values in their daily lives. These findings are expected to contribute conceptually to the development of an adaptive and responsive PAI assessment system in line with the demands of 21st-century education